2011
DOI: 10.5194/tc-5-831-2011
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of snow grain size and albedo of western Himalayan snow cover using satellite data

Abstract: Abstract. In the present study we describe the retrievals of snow grain size and spectral albedo (plane and spherical albedo) for western Himalayan snow cover using Hyperion sensor data. The asymptotic radiative transfer (ART) theory was explored for the snow retrievals. To make the methodology operational only five spectral bands (440, 500, 1050, 1240 and 1650 nm) of Hyperion were used for snow parameters retrieval. The bi-spectral method (440 nm in the visible and 1050/1240 nm in the NIR region) was used to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 67 publications
(81 reference statements)
1
23
0
Order By: Relevance
“…In our case, δ is limited to 0.7 (i.e., a maximum tilt angle for the facet of 63 • ) because for higher values the probability of unphysical scattering events strongly increases, resulting in progressively larger loss of accuracy of the GO calculations of a given number of rays. Neshyba et al (2013) have shown that various other definitions and parameterizations of crystal surface roughness lead to similar results. Yang et al (2008) found that such approaches are efficient yet accurate treatments of microscale roughness.…”
Section: Methodssupporting
confidence: 58%
See 1 more Smart Citation
“…In our case, δ is limited to 0.7 (i.e., a maximum tilt angle for the facet of 63 • ) because for higher values the probability of unphysical scattering events strongly increases, resulting in progressively larger loss of accuracy of the GO calculations of a given number of rays. Neshyba et al (2013) have shown that various other definitions and parameterizations of crystal surface roughness lead to similar results. Yang et al (2008) found that such approaches are efficient yet accurate treatments of microscale roughness.…”
Section: Methodssupporting
confidence: 58%
“…Using instead the 1594 nm channel, diameters typically 30 µm smaller are obtained for each scene, which can be explained by the different penetration depths of the two channels, indicating crystal size increasing with depth as expected Li et al, 2001;Aoki et al, 2000;Warren, 1982). These values, at the lower end of common retrieval ranges, are normally associated with fresh snow conditions as found in studies based on other remote sensors in alpine regions (Negi and Kokhanovsky, 2011;Painter et al, 2009;Dozier and Painter, 2004;Nolin and Dozier, 2000) and polar plateaus (Lyapustin et al, 2009;Hori et al, 2007). However, a direct comparison is challenged by differences in the definition of grain size, assumptions on grain sphericity and different penetration depths achieved by the use of different instrument channels.…”
Section: Resultsmentioning
confidence: 88%
“…(1), the SSA is inversely proportional to the optical radius. Studies reporting on the retrieval of snow properties from satellite data often refer to the optical radius (Fily et al, 1999;Painter et al, 2009;Negi and Kokhanovsky, 2011b), while some others tend to refer to SSA . It is worth noting that the use of SSA is more appropriate when studying small grains with high albedo.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to Nolin and Dozier (1993), for each pixel to be processed, the algorithm searches the LUT and selects the SSA whose computed reflectance spectrum resembles most that of the image according to the spectral distance D defined as…”
Section: Retrieval Methods Based On Look-up Tables Built Using Disortmentioning
confidence: 99%
“…In vast snow areas like the Himalyas, however, adequate field survey is almost impossible and in-situ measurements provide limited regional information (Negi and Kokhanovsky, 2011). Presently, with the use of remote sensing instruments, snow cover information and many other parameters can be determined on real-time, year-round over vast, rugged and remote areas.…”
Section: Snow Depth Distribution Estimation Methods For Mountain Regiomentioning
confidence: 97%